E. GENDROLIO BENDRUOMENINĖS ŽMOGAUS RAIDOS TEORIJA - Mažeikis, Gintautas (Problemos, 2008)
Straipsnyje analizuojami filosofo ir antropologo Edmundo Gendrolio (1938–1994) filosofiniai ntropologiniai samprotavimai apie žmogaus savivokos, save suvokiančio mąstymo raidą. Gendrolis nuosekliai rėmėsi socialinės ir kultūrinės antropologijos teorijomis, empiriniais paleoantropologijos tyrinėjimais, etologijos prielaidomis. Straipsnio tikslas yra parodyti Gendrolio filosofinių antropologinių samprotavimų pecifiškumą, išskiriant jo bendruomeninės abstraktaus mąstymo kilmės teoriją, pabrėžiant solidarumo ir kultūros tvermės formų svarbą žmogaus raidai nuo seniausių Homo erectus laikų. Straipsnyje parodoma, kad Gendrolis nuosaikiai kritikavo marksistinę darbo teoriją, zoologinį individualizmą, linijinį evoliucionizmą, filosofinės antropologijos spekuliatyvumą, ir tvirtinama, kad jis savitai, dialektiškai plėtojo neoevoliucionizmo teorijas, papildytas F. Boaso teorinėmis prielaidomis. Gendrolis atskirai išskyrė istoriškumo bei evoliucijos daugialinijiškumo teorijas, tokiu būdu siekdamas suformuoti savitą sociokultūrinės antropologijos metodologiją ir pasipriešinti unifikaciniam europocentrizmui bei kolonializmui. Pagrindiniai žodžiai: filosofinė antropologija, sociokultūrinė antropologija, neoevoliucionizmas, bendruomeniškumas, darbas, zoologinis individualizmas.E. Gendrolis’ Theory of Communitarian Development of the Human BeingGintautas MažeikisSummaryConsiderations of philosopher and social anthropologists Edmundas Gendrolis (1938–1994) about selfimagination and self-understanding of human beings from the point of social and cultural anthropology and paleoanthropology are analyzed. Gendrolis supported his considerations by theories and ethodologies, researches of social and cultural anthropology, paleoanthropology, ethology, Marxist philosophy. The aim of the article is to show the specificity of his philosophical anthropological considerations, especially of theory of communitarian ideation, development of conscious solidarity, cultural continuity from the time of Homo erectus. The article shows that Gendrolis moderately criticized the Marxist theory of work, zoological individualism, linear evolutionarism, Eurocentrism, racism and cultural segregation. He tried to resist the colonial and neocolonial tendencies in anthropological discourses and to support common po stcolonial attitudes to the history of tribes and small nations. On the contrary, he developed ideas of F. Boas, multilinear cultural Evolutionarism, ideas of L. A. White, M. Sahlins, E. R. Service and the dialectical approach to the complexity of issues of the human being. Such issues are morphological changes of paleoanthropos and neoanthropos, domestic life and household, exogamy and taboo, totems and early forms of faith, tools of the work and art pictures. He tried to develop the humanistic approach to the Homo erectus and Neanderthals as the basis for the future humanistic interpretation of traditional tribes and small nations. Such considerations corresponded to the Lithuanian world conception and to the attempts to liberate themselves from the Soviet occupation and Soviet cultural hegemony. He maintained the main subject of self-comprehending thinking to be community and its skills of cooperation and ideation. Ideation is the process of forming and relating ideas, images and ideals. The process of ideation, the making of abstract solutions and conceptual memory depends on community network, trust, solidarity that could be supported by common rituals, games, art, by the process of education of children. Ideation influenced the skills of hunters, pickers, formed wedding rules, trade among the modern Homini sapiens. And vice versa: all human activities supported and developed the process of abstract thinking and collective ideation. The integral approach to the issues of human being and the theory of multilinear evolution of them became the basis for criticism of Marxist anthropology. He criticized Marxism as well as social Darwinism and any other evolutionism as too much teleological, deterministic and dogmatic theories. His other critical point is about zoological individualism which accumulates a lot of negative interpretations of savages and provides cultural aggression. However, Gendrolis stayed alone from the European social or cultural anthropological movement, and his very large and quite deep considerations didn’t become the beginning of the institutional development of social or cultural anthropological studines in Lithuania. He developed a very little dialog with local ethnologists, and it was the reason for narrow interpretations of his theories. However, his books, articles and ideas are interesting and actual for modern social and philosophical anthropologists.